Análise dos aspectos internos, do ambiente externo e elaboração de cenários como base para a definição das estratégias - Gonçalves, Michele Severo (2011)
This research work, has as objective the development of an evaluation process focused on Internal Aspects, External Environment and Development of Scenarios as base to define strategies on strategic planning. For the realization this work was taken by basis the bibliographic research, of exploratory character and qualitative nature. The goals were reached by a theoretical development, based on analysis of the literature, addressing the constructs: Strategic Planning, Environmental Analysis and Scenario Analysis, by defining concepts, description of its evolution and presentation of implementation models. The process developed in this object is divided into three levels: a) Internal Aspects, the main topics to be analyzed are: Human Resources; Production; Finances; Marketing; Research & Development; analysis of competitive advantages; b) External Environment, the main analyzed variables are: Politics Variables; Economic Variables; Technologic Variables; Demographic Variables; Social Variables; Five Powers of Porter Analysis and the Analysis of attractiveness inside the segment in comparison of all variables; c) Scenario Analysis, are presented nine steps: 1) Identificacion of strategic objectives; 2) Analysis of environmental variables; 3) Selection of key variables; 4) Prospect of scenarios; 5) Relationship of variables with the scenarios; 6) Creation of scenarios; 7) Choice of likely scenarios; 8) Strategies definition; 9) Monitoring scenarios and results using indicators. The Process of Environment Evaluation contributes for that intends to have global organization knowledge, to know the environment and, with analyzing scenarios, preview the future of the organization, to provide solid base to define the strategies.